2009
DOI: 10.1177/1087054708315065
|View full text |Cite
|
Sign up to set email alerts
|

Vigilance and Sustained Attention in Children and Adults With ADHD

Abstract: The present results do not support the hypothesis of a sustained attention deficit in children and adults with ADHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
67
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 92 publications
(78 citation statements)
references
References 59 publications
8
67
0
3
Order By: Relevance
“…Furthermore, our results are Adult ADHD and ISE 18 consistent with those of Tucha et al (2009) who reported preserved sustained attention in adults with ADHD while performing a computerized vigilance task. The finding that adults with ADHD had a lower resistance to auditory interference -but an equivalent capacity to control participants to habituate to repeated and familiar irrelevant sounds -is important in the context of work environments.…”
Section: Sustained Attention and Adhdsupporting
confidence: 89%
“…Furthermore, our results are Adult ADHD and ISE 18 consistent with those of Tucha et al (2009) who reported preserved sustained attention in adults with ADHD while performing a computerized vigilance task. The finding that adults with ADHD had a lower resistance to auditory interference -but an equivalent capacity to control participants to habituate to repeated and familiar irrelevant sounds -is important in the context of work environments.…”
Section: Sustained Attention and Adhdsupporting
confidence: 89%
“…It may also be that children with ADHD require additional cognitive control to compensate for motor deficits (Suskauer, Simmonds, Caffo, et al 2008) and they failed to exert this control either due to deficient in cognitive control, a lack of awareness that additional control was required, or a lack of motivation to exert sufficient control to perform the task efficiently. In addition, a vigilance decrement likely occurred over the course of the task, perhaps to a greater extent for children with ADHD (Tucha et al 2009), and as the attentional system fatigued performance may have become more variable.…”
Section: Discussionmentioning
confidence: 99%
“…This is not surprising considering that the attention deficit is emphasized to laypersons by the name of the condition. Furthermore, both the concepts of attention per se and the attention deficit in ADHD are complex (Cohen 1993;Van Zomeren and Brouwer 1994;Tucha et al 2008;Tucha et al 2009). The difficulties of instructed malingerers in feigning the attention deficit of patients with ADHD are also reflected by the results of Quinn (2003) who found that instructed malingerers are not able to feign a deficit in an integrated visual and auditory continuous performance test.…”
Section: Discussionmentioning
confidence: 99%